Research on the Mechanism and Prevention of Hypertension Caused by Apatinib Through the RhoA/ROCK Signaling Pathway in a Mouse Model of Gastric Cancer - Wang, Wenjuan; Li, Caie; Zhuang, Chenchen; Zhang, Haodong; Wang, Qiongying; Fan, Xin; Qi, Miaomiao; Sun, Runmin; Yu, Jing (Frontiers in Cardiovascular Medicine, 2022)
Hypertension is one of the main adverse effects of antiangiogenic tumour drugs and thus limits their application. The mechanism of hypertension caused by tyrosine kinase inhibitors (TKIs) targeting vascular endothelial growth factors is mainly related to inhibition of nitric oxide (NO) pathway, and activation of endothelin pathway, as well as vascular rarefaction and increased salt sensitivity; consequently, prevention and treatment differ for this type of hypertension compared with primary hypertension. The RhoA/ROCK pathway is involved in the pathogenesis of hypertension related to mediate smooth muscle contraction, eNOS inhibition, endothelial dysfunction and vascular remodeling. In this study, in vivo experiments were performed to explore whether the RhoA/ROCK signalling pathway is part of a possible mechanism of apatinib in the treatment of gastric cancer- induced hypertension and the impairment of vascular remodeling and left ventricular function and to observe whether Y27632 has therapeutic effects. The expression of RhoA/ROCK pathway- related proteins and relative mRNA levels in mice after apatinib intervention were analysed by various methods, and blood pressure and cardiac function indexes were compared. Endothelial and cardiac function and collagen levels in the aorta were also measured to assess vascular and cardiac fibrosis and to provide a basis for the prevention and treatment of this type of hypertension.